PENGARUH LATIHAN CIRCUIT TRAINING TERHADAP MUSCLE ENDURANCE ATLET PANJAT TEBING PEKANBARU NOMOR SPEED TRAX - Saputra, Deni Muliya; Ramadi, Ramadi; Juita, Ardiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The problem in this study is that the athlete's ability is not maximal in displaying his climbing abilities including: 1. Not achieving good time on average which is 10 seconds, 2. Not reaching the top / peak, 3. Not enough energy to reach the top / peak . This is suspected of lack of endurance athletes. The purpose of this study was to determine the effect of circuit training exercises on muscle endurance rock climbing athletes in Pekanbaru Number Speed Trax. The population and sample in this study were Pekanbaru rock climbing athletes Speed Trax Number which numbered 6 people. The instrument used to collect data is pre test and muscle endurance test post with pull up test. The data analysis technique used is the t test. Based on the results of the analysis of pree test and post test data there was an increase of an average of 29.51% with the t test that t = 8.216> of t table = 2015. Then it can be concluded that there is a significant effect of circuit training on muscle endurance rock climbing athletes in Pekanbaru Number Speed Trax.Key Words: Circuit Training Exercises, Muscle Endurance